2019
DOI: 10.32800/amz.2019.17.0034
|View full text |Cite
|
Sign up to set email alerts
|

Check list of waterbirds at Wadi Djedi in Ziban Oasis-Algeria

Abstract: This pioneering work is the first to document the aquatic avifauna community of the Wadi Djedi in the Ziban region in southeast of Algeria. We present results obtained through the monthly counts of waterbirds conducted from September 2013 to September 2016. On this wetland we recorded 36 species of water birds representing 11 families. The Anatidae family was the most numerous, with 11 species. From among all the species, 18 were wintering species, nine were visitors, eight were sedentary breeding species (inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…A maximum of 57 individuals was reported at Djedi stream in November 2014 (Nouidjem et al, 2019), a small population compared to the 1,600 individuals reported at the Oued Righ wetland (Bensaci, Saheb, Nouidjem, Bouzegag, & Houhamdi, 2013;Nouidjem, 2008).…”
Section: Methodsmentioning
confidence: 86%
“…A maximum of 57 individuals was reported at Djedi stream in November 2014 (Nouidjem et al, 2019), a small population compared to the 1,600 individuals reported at the Oued Righ wetland (Bensaci, Saheb, Nouidjem, Bouzegag, & Houhamdi, 2013;Nouidjem, 2008).…”
Section: Methodsmentioning
confidence: 86%
“…We also observed that families such as Laridae and Ardeidae (herons) had the highest number of species after the year 2000 (Figure 5). The previous studies found that herons showed a preference for shallow water and shallow shorelines because these provide suitable food resources (Chettibi et al 2019;Colwell and Taft 2000;Khaing and Sein 2019;Nouidjem et al 2019). Likewise, the gradual desiccation of saline lagoons along the West African coast (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These previous studies reported temporal variation in the numbers of waterfowl according to the seasons of one or two annual cycles. Metallaoui and Houhamdi (2010) reported 47 species belonging to 15 families during one wintering period (August-April); Boudraa et al (2014) recorded 53 species (15 families) over one year; Elafri et al (2016) described 52 species belonging to 13 families over two annual cycles; and Nouidjem et al (2019) reported 36 species, 11 families in the southeast of Algeria. From the point of view of diversity pattern, all these ornithological studies showed that species belonging to the Anatidae family were widely distributed and occurred in all kinds of habitats (open water zone, shore zone, vegetation zone and riparian area) and the gathering and abundance of numerous duck species and coots were conditioned by the diversity of the existing vegetation cover.…”
Section: Discussionmentioning
confidence: 99%
“…From a 'specific richness' aspect, our study area was more frequented during winter, where for both sites a maximum of 42 species was recorded during January ( fig. 2B), thus equaling the ornithological value of the most important wetlands in Algeria (Samraoui et al, 2011;Metallaoui et al, 2014;Benradia et al, 2018;Nouidjem et al, 2019).…”
Section: Diversity Patternsmentioning
confidence: 99%
See 1 more Smart Citation